Feature Article: Transplantation of neuregulin 4-overexpressing adipose-derived mesenchymal stem cells ameliorates insulin resistance by attenuating hepatic steatosis. Issue 7 (May 2019) - Wang, Wenyue; Zhang, Yuxiang; Yang, Chengcan; Wang, Yanni; Shen, Jiahui; Shi, Meilong; Wang, Bing
The aim of this study is to assess whether overexpressing neuregulin 4 (Nrg4), a growth factor known to attenuate hepatic lipogenesis, in mesenchymal stem cells (MSCs) could enhance their ability to ameliorate insulin resistance (IR) and improve lipid metabolism in high-fat diet (HFD)-fed mice. Six-week-old C57BL/6 mice were fed a HFD for 12 weeks and then were given intravenous transplantation of adipose tissue-derived MSCs (ADSCs) or ADSCs overexpressing Nrg4 (Nrg4-ADSCs). Assessment of body weight and blood glucose and insulin levels as well as glucose tolerance test and insulin tolerance test was performed four and eight weeks after cell injection. Triglyceride (TG) and total cholesterol (TC) levels in the plasma and liver were also measured. The mRNA levels of glucose transporter 4 (GLUT4), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) in muscle and adipose tissues were assessed by Real-time Polymerase Chain Reaction (RT-PCR) analysis. Expression of genes related to lipid metabolism, including sterol regulatory element binding protein-1c (SREBP-1c) and fatty acid synthase, was evaluated at the mRNA and protein levels by RT-PCR and western blotting, respectively. The HFD-fed mice receiving ADSCs or Nrg4-ADSCs showed reduced blood glucose levels and enhanced insulin sensitivity, with the Nrg4-ADSC group exhibiting increased improvement in these aspects. HFD-induced changes in the expression of GLUT4 and IL-6 and TNF-α in skeletal muscle and adipose tissues were partially reversed by ADSC or Nrg4-ADSC infusion; however, no difference was observed between these two groups. Nrg4-ADSC-treated mice showed less fat cell deposition and lower TG and TC levels in the serum and liver with decreased expression of SREBP-1c and fatty acid synthase compared with the ADSC group. ADSC transplantation can reduce blood glucose level and ameliorate IR induced by HFD. The protective effects of ADSC can be attributed to suppression of inflammation and augmentation of glucose uptake in skeletal muscle and adipose tissues. More importantly, Nrg4 overexpression in ADSCs could strengthen this efficacy by attenuating hepatic lipogenesis. Impact statement: Due to high-fat and high-sugar diets accompanied by sedentary lifestyles, diabetes has become a global epidemic. Literature findings suggest a potential therapeutic effect of Nrg4 on treating obesity-related metabolic disorders including type 2 diabetes (T2D). Adipose tissue-derived MSCs (ADSCs) were used in our study as they are abundant and can be harvested with minimally invasive procedures. In the end, our study reveals that ADSC transplantation improves glucose tolerance and metabolic balance in HFD-fed mice by multiple mechanisms, including upregulating GLUT4 expression and suppressing inflammation. More importantly, our study shows that Nrg4 overexpression could improve the efficacy of ADSCs in ameliorating insulin resistance (IR) and other obesity-related metabolic disorders, given the function of Nrg4 in attenuating hepatic lipogenesis. It would provide a new therapeutic strategy for the treatment of obesity, IR, and T2D.